The Influence of Using Listen-Read-Discuss (LRD) Strategy towards Students’ Reading Comprehension on Narrative Text - Doni Sudibyo; Agus Setiawan; Anis Rahmawati (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2020)
In this study, the researcher used LRD strategy on narrative text to research The Influence of Using Listen-Read-Discuss (LRD) Strategy towards Students’ Reading Comprehension on Narrative Text at The Eleventh Grade of SMK Muhammadiyah Aimas, Sorong. This research was quantitative research. The researcher used quasi experimental research design. From the data analysis, the objective of this study is to know whether or not there is any significant influence of Listen-Read-Discuss (LRD) strategy towards students’ reading comprehension on narrative text at the eleventh grade of SMK Muhammadiyah Aimas, Sorong. Based on the data analysis, there is a significant influence of using Listen-Read-Discuss (LRD) strategy towards students’ reading comprehension on narrative text at the eleventh grade of SMK Muhammadiyah Aimas, Sorong after the strategy was applied.